2008
DOI: 10.1111/j.1600-0714.2008.00713.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analyses of survivin and heat shock protein 90 expression in patients with oral lichen planus

Abstract: Our results provided additional evidence that alterations in the expression of survivin and Hsp90 in oral epithelia might be associated with pathological stress, such as chronic inflammation, in patients with OLP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 59 publications
4
16
0
2
Order By: Relevance
“…Considering these observations, an increased expression of NLRP3 inflammasome in oral epithelial cells and infiltrated immune cells at the sites of OLP lesional mucosae possibly reflects cellular responses to pathological stimuli. Previous studies have demonstrated aberrant expression of HSP60 and HSP90 in OLP lesions [44,45]. Previous studies have demonstrated aberrant expression of HSP60 and HSP90 in OLP lesions [44,45].…”
Section: Discussionmentioning
confidence: 98%
“…Considering these observations, an increased expression of NLRP3 inflammasome in oral epithelial cells and infiltrated immune cells at the sites of OLP lesional mucosae possibly reflects cellular responses to pathological stimuli. Previous studies have demonstrated aberrant expression of HSP60 and HSP90 in OLP lesions [44,45]. Previous studies have demonstrated aberrant expression of HSP60 and HSP90 in OLP lesions [44,45].…”
Section: Discussionmentioning
confidence: 98%
“…In addition, HSPs can be released extracellularly in response to a number of stressful conditions, but this mechanism, independent of necrotic cell death, is not clear (Tsan and Gao, 2004). Both Sugerman et al (1995) and Chaiyarit et al (2009) detected the expression of hsp70 and hsp90 , respectively in some lymphocytes at the connective tissue in OLP lesions. We should also consider the fact that not all the HSPs, or at least hsp27 , might interact directly with lymphocytes considering the possibility for intermediary molecules carrying out that role.…”
Section: Discussionmentioning
confidence: 94%
“…16,17 The alterations present in the mucosa of OLP patients may involve the homeostatic activities of oral epithelial cells, possibly resulting in an imbalance between cell proliferation and apoptosis. 31 Survivin, a member of IAP family protein, plays a pivotal role in cell survival with a double function: controlling cell division and interacting with several caspases to inhibit apoptosis. 24,25 It is reasonable to think that Survivin is involved in OLP, although studies conducted to date were focused on oral squamous cell carcinoma, [28][29][30] while only one study investigated the expression of Survivin in OLP.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27] There are many studies focused on the relationship between oral squamous cell carcinoma and Survivin, [28][29][30] while the expression of this protein in the context of its relationship to chronic inflammatory diseases were limited, with only one study regarding the expression of survivin in OLP. 31 The aim of this study is to evaluate the expression of OPN, CD44, and Survivin in a group of patients affected by OLP, and assess if there are any differences in the expression levels of these proteins between erosive and reticular form of OLP.…”
Section: Introductionmentioning
confidence: 99%